Pengoperasian Sistem Sensor Gerakan Terhadap Penjimatan Elektrik. Kajian Kes : Menara JLAND, Johor Bahru - Abdullah, Mohamad Zulraihan; Omar, Roshartini (Research in Management of Technology and Business, 2024)
The motion sensor system is the latest technology used to control energy usage, especially in green buildings. However, the operation of this motion sensor system can involve various potential negatives such as lack of technical knowledge, reluctance due to high operating costs, and inaccurate data. Therefore, this study was conducted to achieve objectives such as identifying factors influencing the use of motion sensor systems, examining the effectiveness of operating motion sensor systems, and studying strategies to improve the effectiveness of operating motion sensor systems for electricity savings in Menara JLAND. This study uses a qualitative method, using a questionnaire for interviews to achieve all three research objectives. Respondents selected for interviews are from the facility management involved in operating motion sensor systems at Menara JLAND. The study found that the usage patterns of spaces and occupants' activities are key factors in the operation of motion sensor systems for electricity savings. Meanwhile, the effectiveness of operating motion sensor systems for electricity savings studied is based on the analysis of energy usage data before and after the installation of motion sensor systems. Furthermore, strategies to improve the effectiveness of operating motion sensor systems for electricity savings include using advanced analytical platforms that have proven effectiveness. Therefore, this study is also expected to serve as a reference and source of information for specific parties such as DOSH, CIDB, contractors, academics, and students.